Environmental Reservoirs of Resistance: Detection of MDR Bacterial Isolates from Healthcare Soil Waste - Sharma, Niharika; Kumari, Jyoti; Kumari, Shikha (Journal of Neonatal Surgery, 2025)
The rising threat of antimicrobial resistance (AMR) presents significant challenges to public health, especially when resistant microorganisms emerge from environmental reservoirs such as hospital and pharmaceutical waste sites. In the present study, five soil samples collected from the vicinity of healthcare facilities were screened for microbial isolates. A total of 42 distinct bacterial and 18 fungal isolates were obtained, out of which four bacterial isolates BI4, BT3, HMR2 and TD7 were identified as multidrug-resistant (MDR), showing resistance to more than three antibiotics. Antimicrobial susceptibility testing revealed that TD7 (Pseudomonas aeruginosa) exhibited the highest resistance, being unresponsive to seven antibiotics, while BI4 (P. aeruginosa), BT3 (Bacillus pumilus), and HMR2 (Cellulosimicrobium cellulans) also demonstrated varying degrees of resistance. Notably, C. cellulans (HMR2), a typically non-pathogenic soil bacterium, exhibited resistance to six antibiotics, underscoring the potential role of environmental bacteria in harboring and spreading resistance traits. Biochemical testing, 16S rRNA gene sequencing, and phylogenetic analysis using MEGA 11 confirmed the identity and evolutionary relationships of these isolates. High genetic similarity to clinically relevant strains was observed, particularly among Pseudomonas species, suggesting possible gene exchange between environmental and pathogenic bacteria. The study emphasizes the impact of poorly managed antibiotic disposal and the role of horizontal gene transfer in accelerating resistance development. These findings underline the urgency of implementing robust waste management practices and exploring natural sources for novel antimicrobials to mitigate the growing AMR crisis. The emergence of MDR strains in environmental settings calls for integrative surveillance and preventive strategies.